The prevalence of rhinosinusitis in allergic rhinitis - V Kirtsreesakul (Journal of Health Science and Medical Research (JHSMR), 2006)
Objective: To study the prevalence of rhinosinusitis in allergic rhinitis patients Material and Methods: Sixty adult patients with allergic rhinitis were studied at the Allergy and Rhinology Clinic, Songklanagarind Hospital, between March 1st, 2000 and February 28th, 2006. All patients had a positive skin prick test to at least 1 common aeroallergen. Nasal endoscopy and sinus radiography were performed. The criteria for diagnosis of rhinosinusitis were a history of rhinitis symptoms and a positive nasal endoscopy (mucoid or mucopurulent discharge from middle meatus or superior meatus) and/or abnormal sinus radiography. Results: Of the 60 patients with allergic rhinitis, 59 (98.3%) demonstrated sensitivity to more than 1 aeroallergen – most prominently, Dermatophagoides pteronyssinus (80.4%) and Dermatophagoides farinae (71.4%). Thirty two (53.3%) had an abnormal sinus radiography and 14 (23.3%) had a positive nasal endoscopy. According to rhinosinusitis diagnostic criteria, 32 (53.3%) had rhinosinusitis. Conclusion: 53.3% of patients with allergic rhinitis had rhinosinusitis, showing association between these two common diseases.